The role of circulating free DNA in the management of NSCLC. Issue 1 (2nd January 2019) - Esposito Abate, Riziero; Pasquale, Raffaella; Fenizia, Francesca; Rachiglio, Anna Maria; Roma, Cristin; Bergantino, Francesca; Forgione, Laura; Lambiase, Matilde; Sacco, Alessandra; Piccirillo, Maria Carmela; Morabito, Alessandro; Normanno, Nicola
ABSTRACT: Introduction : Circulating cell-free DNA (cfDNA) testing has emerged as an alternative to tumor tissue analyses for the management of metastatic non-small-cell lung cancer (NSCLC) patients. Analysis of cfDNA is a minimally invasive procedure that might better reflect tumor heterogeneity and allows repeated testing over the time. Areas covered : This review article covers the different applications of cfDNA testing in NSCLC: early diagnosis of the disease; detection of minimal residual disease in early lung cancer; identification of predictive and prognostic markers in advanced NSCLC patients; monitoring the response to therapy; assessment of tumor mutation burden. Expert commentary : The use of liquid biopsy is rapidly expanding to different applications. The combination of different circulating biomarkers (cfDNA, protein, miRNA) might improve the sensitivity and specificity of this approach in patients with low tumor burden. cfDNA testing is representing a valid source for molecular profiling in management of metastatic NSCLC patients and is providing important knowledge on tumor heterogeneity. Clinical trials are needed in order to transfer the information deriving from liquid biopsy testing in new therapeutic strategies.